Should I stay or should I go? Bank productivity and internationalization decisions - Buch, Claudia M.; Koch, Cathérine T.; Koetter, Michael (Journal of Banking & Finance, 2014)
Differences in firm-level productivity explain international activities of non-financial firms quite well. We test whether differences in bank productivity determine international activities of banks. Based on a dataset that allows tracking banks across countries and across different modes of foreign entry, we model the ordered probability of maintaining a commercial presence abroad and the volume of banks’ international assets empirically. Our research has three main findings. First, more productive banks are more likely to enter foreign markets in increasingly complex modes. Second, more productive banks also hold larger volumes of foreign assets. Third, higher risk aversion renders entry less likely, but it increases the volume of foreign activities conditional upon entry.